A Voice from Beyond. The Story of the Deirdre Story - Tallone, Giovanna (ABEI Journal, 2011)
The multiple life of the story of Deirdre and the Sons of Uisneach in the Literary Revival has its roots in the multiple life of its sources. Thoughmainly connected to the wide range of drama renditions in the background of the Irish Dramatic Movement, the Deirdre story is first of all a narrative concerning language. The Old Irish Version, Longes mac N-Uisleann (The Exile of the Sons of Uisneach) opens with a speech act below the level of articulation, unborn Deirdre’s cry from her mother’s womb. The prophecy of destruction that follows is thus a prescribed text. In medieval versions and folklore renditions, including the Middle Irish text, Oidhe Chloinne Uisneach (The Violent Death of the Children of Uisneach) the detail disappears or it is developed otherwise. However, in its various versions and remakes, words and language are relevant,as taboos, oaths and mutually exclusive words represent a structuring principle. The purpose of this essay is to examine the sources of the Deirdre story and its prose remakes in the nineteenth and early twentieth century, with particular reference to Standish O’Grady, Lady Gregory and James Stephens, shedding light on the way the power of language that characterises the old legend is developed in different cultural contexts.